Chemoprevention targets for tobacco-related head and neck cancer: Past lessons and future directions. Issue 6 (June 2015) - Sheth, Siddharth H.; Johnson, Daniel E.; Kensler, Thomas W.; Bauman, Julie E.
Summary Progress toward identifying an effective chemopreventive agent to reduce the incidence of head and neck squamous cell carcinoma (HNSCC) has been limited by poor efficacy and intolerable toxicity profiles. In this review, we summarize the biological basis of HNSCC chemoprevention, and outline challenges associated with identifying appropriate high-risk HNSCC populations for chemoprevention studies. We discuss findings and lessons learned from clinical trials that have investigated micronutrient and molecular targeting interventions. Finally, we introduce the concept of green chemoprevention, interventions based upon whole plant foods or simple extracts that may represent a safe and cost-conscious option for the next generation of studies. As our scientific understanding of HNSCC reaches new levels, the field is poised to develop chemoprevention studies based on rigorous biological validation with accessibility to all affected individuals regardless of socioeconomic barriers.